(untitled) (World Science, 2023)
Research aim. to assess the impact of post-traumatic stress on the risk of carbohydrate metabolism disorders in concussed female veterans. Systematization of multidisciplinary analysis and obtained data on the impact of PTSD on the development and course of carbohydrate metabolism disorders. Material and methods. A comprehensive clinical and laboratory examination of women veterans with PTSD and women from the comparison group was carried out. Group I consisted of examination data of women who suffered contusion during combat operations with PTSD, group II – control one, consisted of healthy women. Complaints, obstetric – gynaecological and somatic history were studied in detail, anthropometric data, the state of carbohydrate metabolism, and mental health were assessed. Results and conclusions. The results of the conducted research show that the correction of carbohydrate metabolism disorders and treatment of pre-existing pathology caused by the influence of stress factors in combatants in order to preserve reproductive health is expedient and necessary.